A comparative study of proton conduction between two new Cd(II) and Co(II) complexes and in vitro antibacterial study of the Cd(II) complex. (24th October 2022) - Li, Yuyan; Li, Duqingcuo; Qin, Tianrui; Shi, Zhan; Fu, Pengkun; Xiong, Dingqi; Dong, Xiuyan
Abstract : Two new complexes based on 4, 4′‐[1, 3‐phenylenebis(oxy)]diphthalic acid (H4 L) ligands were synthesized, namely, [Cd2 (L)(1, 10‐phen)2 (H2 O)]n (1 ) and [Co2 (L)(1, 10‐phen)2 (H2 O)]n (2 ), in which 2D structures transform into 3D supramolecular structures by CH···π interaction. The proton conductivity of complexes 1 and 2 at low temperature is close (σ1  = 3.12 × 10 −8  S cm −1 and σ2  = 3.81 × 10 −8  S cm −1 at 30°C), but these two complexes show different conduction mechanisms. The Vehicular mechanism in 1 is caused by the O···H/H···O contact in 1, which is stronger than 2, and the Grotthuss mechanism in 2 is caused by the N···H/H···N contact in 2, which is stronger than 1 . At the same time, complex 1 showed excellent antibacterial properties in vitro, mainly reflected in that five kinds of bacteria ( Escherichia coli, Bacillus amyloliquefaciens, Pantoea agglomerans, Pseudomonas putida, and Pectobacterium carotovora ) could play an obvious inhibitory effect in the concentration range of 20 μg·ml −1 . Abstract : Two complexes based on 4, 4′‐[1, 3‐phenylenebis(oxy)]diphthalic acid (H4 L) ligands were synthesized, namely, [Cd2 (L)(1, 10‐phen)2 (H2 O)]n (1 ) and [Co2 (L)(1, 10‐phen)2 (H2 O)]n (2 ). In these two complexes, 2D structures transform to 3D supramolecular structures by CH···π interaction. These two complexes show different conduction mechanisms in the proton conduction test, complex 1 shows the Vehicular mechanism and complex 2 shows the Grotthuss mechanism. The minimum inhibitory concentrations (MICs) results showed that all five kinds of bacteria ( Escherichia coli, Bacillus amyloliquefaciens, Pantoea agglomerans, Pseudomonas putida, and Pectobacterium carotovora ) could play an obvious inhibitory effect in the concentration range of 20 μg·ml −1 .